DEVELOPING VOCABULLARY MASTERY OF GRADE SEVEN STUDENTS OF SMPN 6 PALU THROUGH CARTOON MOVIES - Widyaningrum, Thalita Putri; Mukrim, Mukrim; Anggreni, Afrillia (Tadulako University, 2024)
The purpose of this research is to determine if the use of cartoon movies can develop the vocabulary mastery of grade seven students of SMPN 6 Palu. This research method used a quasi-experimental. The population of this research are students of grade seven of SMPN 6 Palu consists of two classes, with the total number is 239 people. The cluster random sampling technique is used to determine the sample of control class and the experimental class. Based on this technique, class VII A became the control group and VII F was the experiment group. The instruments used in this research consisted of pre-test and post-test, there were three kinds of the test; spelling words, matching, and making sentences. In the pre-test, the mean scores of the experimental group was 85,93 and the control group was 86.15. The post-test result for the experimental group was 96,85 and for the control group was 95,22. Applying a significance level of 0.05, the researcher found that the t-count (2,982) was higher than the t-table (1.671). Therefore, Ho is declared rejected and Ha is accepted. In conclusion, the use of cartoon movies can develop the vocabulary mastery of the grade seven students of SMPN 6 Palu.